Negation in Negationless Intuitionistic Mathematics. Issue 1 (21st October 2022) - Ferguson, Thomas Macaulay
Abstract: The mathematician G.F.C. Griss is known for his program of negationless intuitionistic mathematics . Although Griss's rejection of negation is regarded as characteristic of his philosophy, this is a consequence of an executability requirement that mental constructions presuppose agents' executing corresponding mental activity. Restoring Griss's executability requirement to a central role permits a more subtle characterization of the rejection of negation, according to which D. Nelson's strong constructible negation is compatible with Griss's principles. This exposes a 'holographic' theory of negation in negationless mathematics, in which a full theory of negation is 'flattened' in a putatively negationless setting.